Barriers to Adopting a Fistula-First Policy in Europe: An International Survey among National Experts. Issue 2 (March 2015) - van der Veer, Sabine N.; Ravani, Pietro; Coentrão, Luis; Fluck, Richard; Kleophas, Werner; Labriola, Laura; Hoischen, Susanne H.; Noordzij, Marlies; Jager, Kitty J.; van Biesen, Wim
Purpose: The purpose of this study is to explore how vascular access care was reimbursed, promoted, and organised at the national level in European and neighbouring countries. Methods: An electronic survey among national experts to collect country-level data. Results: Forty-seven experts (response rate, 76%) from 37 countries participated. Experts from 23 countries reported that 50% or less of patients received routine pre-operative imaging of vessels. Nephrologists placed catheters and created fistulas in 26 and 8 countries, respectively. Twenty-one countries had a fee per created access; the reported fee for catheter placement was never higher than for fistula creation. As the number of haemodialysis patients in a centre increased, more countries had a dedicated coordinator or multidisciplinary team responsible for vascular access maintenance at the centre-level; in 11 countries, responsibility was always with individual nephrologists, independent of a centre's size. In 23 countries, dialysis centres shared vascular access care resources, with facilitation from a service provider in 4. In most countries, national campaigns (n = 35) or educational programmes (n = 29) had addressed vascular access-related topics; 19 countries had some form of training for creating fistulas. Forty experts considered the current evidence base robust enough to justify a fistula-first policy, but only 13 believed that more than 80% of nephrologists in their country would attempt a fistula in a 75-year-old woman with comorbidities. Conclusions: Suboptimal access to surgical resources, lack of dedicated training of clinicians, limited routine use of pre-operative diagnostic imaging and patient characteristics primarily emerged as potential barriers to adopting a fistula-first policy in Europe.